The Effect of Price Promotion, Trust, Perceived Usefulness, and Perceived Ease of Use towards the Customer Continuace Intention to Use GO-PAY - Alexander Wijaya (iBuss Management, 2019)
The market for financial technology industry in Indonesia is keep growing. There are some big players in it and one of the biggest is GO-PAY. In order to attract the customer to continuesly use the financial technology services there are some factors that should be taken into account for. This research aims to know the effectiveness of four independent variables, namely price promotion, trust, perceived usefulness, and perceived ease of use towards the customer continuance intention to use GO-PAY.The data for this research were gathered through simple random sampling with 89 questionnaires. Then, the data were processed by using Multiple Linear Regression Analysis. It is found that only price promotion, and perceived ease of use that impact customer continuance intention to use individually. Keyword:Price Promotion, Trust, Perceived Usefulness, Perceived Ease of Use, Continuance Intention to Use